PARTY PUBLICATIONS AS THE MAIN PUBLIC REFLECTION OF POLITICAL PROCESSES - Mansurov Davron Asilhodjaevich (Galaxy International Interdisciplinary Research Journal, 2024)
During the еars of independence, the political system of Uzbekistan carried out great work on the liberalization of society, and the foundations of democratic statehood were created that meet the highest interests of our people. In recent еars, the processes of improving the institutions of civil society, which are directly involved in ensuring the rights, freedoms and legal interests of citizens, and the liberalization of the political system, are deepening more and more. In particular, political pluralism, that is, building an enlightened society based on the diversity of opinions and views, as well as the role of political party publications in achieving our lofty goals, is incomparable. This article analyzes the development leaders of political parties operating in the process of deepening democratic reforms and the formation of civil society in the Republic of Uzbekistan, as well as the ideologies they rely on.